Effect of Water Saturation Changes on the Creep and Stability of the Soil Slope Parallel to the Al-Qawasim Mountain Road - Alakhdar, Aboalgasem (Sharwes Scientific Journal, 2025)
The study aims to evaluate the effect of internal water saturation on the stability of the soil slope parallel to Al-Qawasem Road by testing water quantities of 60, 70, and 80 mm and assessing their impact on soil cohesion and  friction angle. To achieve this, field observations, laboratory experiments, and numerical simulations using the RocPlan program were conducted. Field data revealed the inclination of tree trunks, indicating ongoing soil creep. Laboratory results showed that increasing the internal saturation ratio from 16.5% to 19.5% led to a significant decrease in cohesion and friction angle, thereby reducing soil resistance. The simulation results confirmed a decrease in the safety factor from 1.002 to 0.3, classifying the slope as being in the "choking stage" a critical condition that necessitates continuous monitoring and preventive measures.